Base‐Sequence‐Independent Efficient Redox Switching of Self‐Assembled DNA Nanocages. (18th September 2019) - Wang, Bang; Song, Lei; Jin, Bang; Deng, Ning; Wu, Xiaojing; He, Jianbo; Deng, Zhaoxiang; Li, Yulin
Abstract: Stimuli responsivity has been extensively pursued in dynamic DNA nanotechnology, due to its incredible application potentials. Among diverse dynamic systems, redox‐responsive DNA assembly holds great promise for broad applications, especially considering that redox processes widely exist in various physiological environments. However, only a few studies have been reported on redox‐sensitive dynamic DNA assembly. Albeit ingenious, most of these studies are either dependent on the DNA sequence or involve chemical modification. Herein, a facile and universal mechanism to realize redox‐responsive self‐assembly of DNA nanocages (tetrahedron and cube) driven by the interconversion between cystamine and cysteamine toward dynamic DNA nanotechnology is reported. Abstract : Dynamic DNA : A facile and universal mechanism to realize redox‐responsive self‐assembly of DNA nanocages (tetrahedra and cubes) is reported. This process is driven by reversible chemical conversion between cystamine and cysteamine and could lead to applications in dynamic DNA nanotechnology.